2017
DOI: 10.5853/jos.2016.01368
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of microRNAs in Ischemic Stroke: As Possible Therapeutic Agents

Abstract: Stroke is one of the leading causes of death and physical disability worldwide. The consequences of stroke injuries are profound and persistent, causing in considerable burden to both the individual patient and society. Current treatments for ischemic stroke injuries have proved inadequate, partly owing to an incomplete understanding of the cellular and molecular changes that occur following ischemic stroke. MicroRNAs (miRNA) are endogenously expressed RNA molecules that function to inhibit mRNA translation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(95 citation statements)
references
References 249 publications
(262 reference statements)
3
83
0
3
Order By: Relevance
“…And circulating miR‐15a and miR‐16 are enriched in critical limb ischaemia (CLI) patients and serum miR‐15a expression is also positively associated with post‐revascularization restenosis 173. A recent study reported that circulating miR‐363, miR‐487b, miR‐125b‐2, miR‐27a, miR‐422a, miR‐488, miR‐627, miR‐290, miR‐10a, miR‐182, miR‐200b, miR‐298, miR‐106b‐5p and miR‐4306 are increased while circulating miR‐122, miR‐148a, let‐7i, miR‐19a, miR‐320d, miR‐4429, miR‐30a, miR‐126, miR‐9, miR‐219, miR‐320e and miR‐320d are reduced following ischaemic stroke 174. Interestingly, miR‐10a contributes to the repression of pro‐inflammatory endothelial phenotypes in atherosusceptible regions in vivo 167.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 99%
“…And circulating miR‐15a and miR‐16 are enriched in critical limb ischaemia (CLI) patients and serum miR‐15a expression is also positively associated with post‐revascularization restenosis 173. A recent study reported that circulating miR‐363, miR‐487b, miR‐125b‐2, miR‐27a, miR‐422a, miR‐488, miR‐627, miR‐290, miR‐10a, miR‐182, miR‐200b, miR‐298, miR‐106b‐5p and miR‐4306 are increased while circulating miR‐122, miR‐148a, let‐7i, miR‐19a, miR‐320d, miR‐4429, miR‐30a, miR‐126, miR‐9, miR‐219, miR‐320e and miR‐320d are reduced following ischaemic stroke 174. Interestingly, miR‐10a contributes to the repression of pro‐inflammatory endothelial phenotypes in atherosusceptible regions in vivo 167.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 99%
“…A full accounting of the potential role of miRNAs as therapeutic targets or agents for ischemic stroke is beyond the scope of our review and the reader is referred to some recent articles on the topic (Chandran et al, 2017; Gaudet et al, 2017; Kaur et al, 2018; Khoshnam et al, 2017). Rather, we focus on several miRNAs that have garnered considerable interest and are illustrative of the potential benefits and challenges of this approach.…”
Section: Recently Identified Molecular/cellular Targets and Approachesmentioning
confidence: 99%
“…Through the post‐transcriptional regulation of gene expression, miRNAs are believed to regulate various biological processes, including proliferation, apoptosis, the cell cycle, and differentiation, that are involved in both physiological and pathological progress . Currently, accumulating evidence indicates that various miRNAs are dysregulated in cerebral ischaemia/reperfusion injury and can be potentially used as diagnostic and/or therapeutic targets . Various studies demonstrated that targeting specific miRNAs can alleviate neuronal injury and recover neurological functions using in vitro and in vivo experimental models of cerebral ischaemia/reperfusion injury .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Currently, accumulating evidence indicates that various miRNAs are dysregulated in cerebral ischaemia/ reperfusion injury and can be potentially used as diagnostic and/or therapeutic targets. 13,14 Various studies demonstrated that targeting specific miRNAs can alleviate neuronal injury and recover neurological functions using in vitro and in vivo experimental models of cerebral ischaemia/reperfusion injury. [15][16][17][18] However, the precise miRNA-mediated epigenetic regulatory mechanism in cerebral ischaemia/reperfusion injury remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%